Analisis Penilaian Tingkat Kesehatan Bank Dengan Menggunakan Metode RGEC Pada PT Bank Cimb Niaga, Tbk Tahun 2014-2023 - Abdul Karim; Hendri Prasetyo (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This study aims to examine and analyze the level of bank health using the Risk Profile, Good Corporate Governance, Earnings, and Capital (RGEC) approach at PT Bank CIMB Niaga Tbk in 2014-2023. The type of research used is descriptive research with a quantitative approach. The results of this study indicate that the level of health of PT Bank CIMB Niaga Tbk in 2014 to 2023 as measured using the RGEC approach can be said to be Healthy. Judging from the Risk Profile factor assessed by the NPL, LDR, and IRR ratios, overall it is categorized as Healthy. In the Good Corporate Governance factor, PT Bank CIMB Niaga already has and implements Good Corporate Governance. In the Earnings factor assessed by the ROA, NIM, and ROE ratios, overall it is categorized as Healthy. In the Capital factor assessed by the CAR ratio, it gets the predicate Very Healthy.